Application of Clove Leaf Oil (Syzygium aromaticum L.) on Preservation of Milkfish (Chanos chanos) - Rukmawati Rukmawati; Daud K. Walanda; Irwan Said (Jurnal Akademika Kimia, 2021)
Clove leaf oil (Syzygium aromaticum L.) is obtained from distilling clove leaves. This study aimed to examine the effect of clove leaf oil on the preservation of milkfish meat. Clove leaf oil was obtained by steam distillation and purified by a simple distillation method. The number of microbes was determined using the total plate count (TPC) method, while the organoleptic test used a level of preference for color, smell, texture, and taste. The results showed that the pH and the number of fish meat bacteria at a concentration of 8%, when left for one day, were 6.61 and 2.46 × 10-7 CFU/mL, while the three days was 7.2 and 2.98 × 10-7 CFU/mL, a concentration of 10% in 1 day which was 6.64 and 2.03×10-7 CFU/mL while the three days was 7.25 and 2.54 × 10-7 CFU/mL and a concentration of 12 % in 1 day was 6.67 and 1.83 × 10-7 CFU/mL while three days was 7.57 and 2.07 × 10-7 CFU/mL, besides that from organoleptic test data the panelist preference rate was more significant in the concentration of 12 % then the concentration of 10  and 8 %, respectively. The results showed that at a concentration of 12%, it was a good concentration to be used as preservation compared to a concentration of 10 % and a concentration of 8%, both for a 1-day and a 3-days. This shows that the higher the concentration of clove leaf oil, the greater the ability to preserve fish meat.